RISIKO BENCANA TANAH LONGSOR DI DESA CIHANJUANG KECAMATAN CIMANGGUNG KABUPATEN SUMEDANG JAWA BARAT - Fachry Arsyad; Ade Subarkah (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2023)
This study aims to understand the risks of landslides that can occur in Cihanjuang Village, Cimanggung District, Sumedang Regency, West Java. The research method used is qualitative research, in order to get a comprehensive picture of the risk of landslides, at the research location. The types of data sources consist of primary data sources originating from disaster activists in Cihanjuang Village, and secondary data obtained from supporting informants, such as community leaders, government officials, disaster volunteers, and other supporting data. Data collection was carried out by interviews, documentation studies, observations, and Focus Group Discussions. Checking the validity of the data performs confirmability testing. Data analysis in this study used qualitative analysis, which consisted of data reduction, data presentation, and drawing conclusions. The results showed that the village was at risk of landslides. This was concluded by the existence of multiple threats, multiple vulnerabilities and the capacity of the community that was not ready to face the impact of a disaster. This condition is coupled with the construction of settlements carried out both by non-governmental organizations, developers, and the government with a subsidized housing program, using relatively steep hillsides as settlement construction sites.